2000
DOI: 10.1097/00000658-200008000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Rejection of Renal Allografts From Brain-Dead Donors

Abstract: ObjectiveTo define the potential influences of donor brain death on organs used for transplantation. Summary Background DataDonor brain death causes prompt upregulation of inflammatory mediators on peripheral organs. It is hypothesized that this antigen-independent insult may influence the rate and intensity of host alloresponsiveness after engraftment. MethodsThe rates of survival of unmodified Lew recipients sustained by kidney allografts from brain-dead, normal anesthetized, and anesthetized ventilated F344… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
118
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(124 citation statements)
references
References 27 publications
4
118
0
2
Order By: Relevance
“…Namely, plasma levels of IL-8 were also found associated with mortality after cardiopulmonary resuscitation (Adrie et al 2002), with acute respiratory distress syndrome (ARDS) (Imai et al 2003) and in experimental model of braindead donors (Pratschke et al 2000). Even postmortem analysis of IL-8 indicated in one study its association with severe traumatic injury (Mimasaka 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Namely, plasma levels of IL-8 were also found associated with mortality after cardiopulmonary resuscitation (Adrie et al 2002), with acute respiratory distress syndrome (ARDS) (Imai et al 2003) and in experimental model of braindead donors (Pratschke et al 2000). Even postmortem analysis of IL-8 indicated in one study its association with severe traumatic injury (Mimasaka 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The raise of IL-8 in CSF can be also found in various neurological syndromes in particular in neurodegenerative diseases (Stoeck et al 2006). Even in case of moderate brain injury, prompt expression of mRNA of cytokines, chemokines and adhesion molecules was found (Pratschke et al 2000). It is speculated that these events eventually lead to dysregulation of apoptosis (Papathanassoglou et al 2001), which plays important role in multiple organ dysfunction syndrome (MODS).…”
Section: Discussionmentioning
confidence: 99%
“…It is recognized that brain death has defined effects on hemodynamic stability, hormone regulation, and inflammatory reactivity that predispose for additional organ injury during hypothermic preservation and reperfusion after transplantation (7). In this regard, brain death is associated with structural myocardial damage (31), intense nonimmune inflammation in kidney isografts (8), and higher incidence of acute and chronic allograft rejection (12,(32)(33)(34). This study represents the first examination of brain death's impact on islet recovery and functionality in vitro and in vivo after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several groups have reported a significant increase in the concentrations of pro-inflammatory cytokines such as interleukin-1 (IL-1), IL-2, IL-6, and tumor necrosis factor-alpha (TNFα). (Skrabal et al 2005;Pratschke et al 2000;Shohami et al 1994) Additionally, the neutrophil chemokine, IL-8, has also been demonstrated to be elevated in the lungs of BD lung donors. (Fisher et al 1999) Increased neutrophil burden has been strongly associated with increased matrix-metalloprotease activity and possible exposure of the autoantigen collagen V (Coll V).…”
Section: Other Donor Factorsmentioning
confidence: 99%